Aplikasi Pola Paternalistik dan Pola Konsumeristik dalam Informed Consent - sarsintorini putra (Jurnal Hukum IUS QUIA IUSTUM, 2000)
Everybody has the right self-determination about what will be done for his/herself, and he or she also has the right to obtain healthcare as well as the right of information. As consequence, all medical-affairs should obtain consent from the patient or his/her family. The agreement is provided to the patient after she/he gets informed adequately about the importance of medical care with the possibly arising risk. The ground informed consent isan agreement between a doctor and his/her patient. Hence, the doctor who has done a surgery, for Instance, invasively without any permission from the patient is considered breaking the law and is responsible for the patient's injury. In order,that the doctor's information is clear forthe patient—which can hindera conflict— the use of paternalistic pattern and of consumerism pattern are recommended as the ground for the process of informed consent making.